ANALYSIS OF HYDROCARBON TREATING SYSTEM TO THE EMISSION OFF SPARK-IGNITION FOUR-STROKE ENGINE - Binyamin Binyamin; Subroto Subroto; Tri Tjahjono (Program Studi Teknik Mesin, Universitas Muhammadiyah Surakarta, 2014)
The reduction of carbon monoxide (CO), unburnthydrocarbon (UHC) emission and fuel consumption on spark-ignition four-stroke engine is continuously attempted. The purposes from this research were to determine the effect of Hydrocarbon Treating System (HTS) on levels of CO, UHC and fuel consumption. This is an experimental research. Its is conducted by comparing the exhaust pollutant concentration such as carbon monoxide, unburnt hydrocarbon and also fuel consumption between standard engine setting and Hydrocarbon Treating System applied. The research variable are HTS flow rate from Q1 = 0 cc/s (without HTS), Q2 = 1,5 cc/s, Q3 = 2 cc/s, Q4 = 2,5 cc/s, and Q5 = 33 cc/s. The research will be done in three conditions which are low, medium and high rotation. The result showed that Hydrocarbon Threating System decrease fuel consumption up to 19,43% with flow rate Q5 = 3 cc/s, but on the other hand it increase CO emission up to 80.84% with flow rate Q5 = 3 cc/s and UHC emission level up to 124.75% with flow rate Q5 = 3 cc/s from engine standart condition.